2011
DOI: 10.3402/fnr.v55i0.7153
|View full text |Cite
|
Sign up to set email alerts
|

Intake of micronutrients among Danish adult users and non-users of dietary supplements

Abstract: ObjectivesTo evaluate the intake of micronutrients from the diet and from supplements in users and non-users of dietary supplements, respectively, in a representative sample of the Danish adult population. A specific objective was to identify the determinants of supplement use.DesignA cross-sectional representative national study of the intake of vitamins and minerals from the diet and from dietary supplements.MethodThe Danish National Survey of Dietary Habits and Physical Activity, 2000–2004. Participants (n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
55
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 17 publications
13
55
0
1
Order By: Relevance
“…Like our study, Tetens and colleagues also found that the differences in nutrient intakes were much more evident among women than men (25). This is an interesting finding, and may indicate that female supplement users exhibit different eating patterns (ie, more nutrient dense) than male supplement users.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Like our study, Tetens and colleagues also found that the differences in nutrient intakes were much more evident among women than men (25). This is an interesting finding, and may indicate that female supplement users exhibit different eating patterns (ie, more nutrient dense) than male supplement users.…”
Section: Discussionsupporting
confidence: 79%
“…Tetens and colleagues (25) have recently published estimates of micronutrient intakes by supplement use from the Danish National Birth Cohort. Like our study, Tetens and colleagues also found that the differences in nutrient intakes were much more evident among women than men (25).…”
Section: Discussionmentioning
confidence: 99%
“…Some report a more frequent use among women (Nieper, ; Skeie et al., ; Tscholl et al., ; Tetens et al., ; Wiens et al., ), others in men (Goston & Toulson Davisson Correia, ; Diehl et al., ; El Khoury & Antoine‐Jonville, ; Giannopoulou et al., ), while others report no gender differences (Erdman et al., ; Suzic Lazic et al., ). The conflicting results may be due to athletic status, health status, and demographics as it has been shown that athletes use more NS than non‐athletes (Sundgot‐Borgen et al., ; Giannopoulou et al., ), that the use of NS correlates with increased physical activity (Kirk et al., ; Tetens et al., ; Pouchieu et al., ) and “good health” (i.e., a healthy diet, no smoking, a low alcohol intake, and a high level of physical activity) (Kirk et al., ; Tetens et al., ; Bailey et al., ; Pouchieu et al., ), and that NS use vary with geographic origin for both athletes (Tscholl et al., ; Giannopoulou et al., ) and the general population (Skeie et al., ; Bailey et al., ). These factors might explain the gender difference in this study, as women in developed countries engage to a larger extent in health activities than men (e.g., Rice, ; Ek, ), and because Denmark is a high NS‐use country with a greater frequency of use among women than men in the general population (Skeie et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In a large scale study in Danish population involving over 4000 participants, it was observed that more than half of the study subjects were users of these micronutrient dietary supplements. This usage increased with age and with ‘intention to eat healthy’[3]. In a drug utilisation study in secondary care hospitals in Maharashtra, India, it was found that in 16% of the prescriptions, a multivitamin product was prescribed.…”
mentioning
confidence: 99%
“…Our research examines the various vitamin supplements available to the consumer in India. Many studies report an increase in the use of such dietary supplements by the population at large[236]. However, current detailed data on the prevalence of supplement use, characteristics of users and their relation to health and nutrition are lacking in Indian population.…”
mentioning
confidence: 99%